2003
DOI: 10.1063/1.1619976
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dust-charge fluctuations on the potential of an array of projectiles in a partially ionized dusty plasma

Abstract: The expressions for the Debye and the wake potential are derived by incorporating dust-charge fluctuations of a single projectile, as well as of an array of dust grain projectiles, propagating through a partially ionized dusty plasma with a constant velocity. Numerically, the effects of the dust-charge fluctuations and the dust–neutral collisions on the electrostatic potential for a single, three, six and ten projectiles are examined. The dust-charge relaxation rate modifies the shape of the Debye as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Now solving the DH potential first, we need to express the wave, position, and velocity vectors into spherical polar coordinates (Yaqoob et al, 2002;Ali et al, 2003), respectively, as k (k sin θ k cos ϕ k , k sin θ k sin ϕ k , k cos θ k ), r (r sin θ r cos ϕ r , r sin θ r sin ϕ r , r cos θ r ), and v T (0, 0, v T ).…”
Section: Potential Distribution Around the Resonating Test Chargementioning
confidence: 99%
See 1 more Smart Citation
“…Now solving the DH potential first, we need to express the wave, position, and velocity vectors into spherical polar coordinates (Yaqoob et al, 2002;Ali et al, 2003), respectively, as k (k sin θ k cos ϕ k , k sin θ k sin ϕ k , k cos θ k ), r (r sin θ r cos ϕ r , r sin θ r sin ϕ r , r cos θ r ), and v T (0, 0, v T ).…”
Section: Potential Distribution Around the Resonating Test Chargementioning
confidence: 99%
“…After some more simplifications, Eq. 14 is finally reduced to the following result (Ali et al, 2003)…”
Section: Potential Distribution Around the Resonating Test Chargementioning
confidence: 99%
“…Test charge techniques [12,13] can be utilized to study the shielding of test charges in collisional [14] and turbulent [15] plasmas, the electric field [16], and farfield potential of a test charge in a nonuniform magnetoplasma [17], the wake-field excitations in charge fluctuating dusty plasmas [18], the two-body correlations [19], the energy loss of test charges [20], etc. If a test particle is projected into the plasma with a constant speed, its charge density is coupled with the plasma charge density by the space charge effects.…”
Section: Dusty Plasma and Test Charge Techniquementioning
confidence: 99%
“…It was found that external magnetic field and ion-streaming effects [40,41] strongly affect the positive/negative potential regions in plasmas. To explore the effects of two-body correlations, dust-charge perturbations and dustneutral collisions, various geometries have been designed for propagating test charges [18][19][20] in an unmagnetized Maxwellian dusty plasma. In all above investigations, the plasma particles are described by the Maxwellian distribution function.…”
Section: Dusty Plasma and Test Charge Techniquementioning
confidence: 99%
“…Quantum plasma's are generally made of electrons and ions or holes. The studies on quantum plasma got importance in several branches of applied physics specially in nano-science [19][20][21] as well as in laboratory plasma experiments [22][23][24][25] and in astrophysical scenario [26][27][28]. Pine [29] have treated an arbitrary collision-less quantum plasma environment as a dielectric medium and derived the analytic form of dielectric function using Random Phase Approximation (RPA) method.…”
Section: Introductionmentioning
confidence: 99%